(untitled) (Development Service Industry Management, 2023)
The research focuses on the need to implement in Ukraine new approaches to ensuring social security, namely such a tool as consumer security. The purpose of the research is to substantiate the directions of activation of the policy of consumer security in the direction of modernization of the economic security system of Ukraine. The author’s definition of the concept of "consumer safety" is given as a policy initiated by the state and implemented at all levels (individuals, enterprises, communities, regions, countries), aimed at changes, shifts, improvement of structural characteristics and relationships in the system of social reproduction (production → distribution → exchange → consumption) in order to achieve positive effects in the field of food security, quality of life and well-being of society, ecology, sustainable development, information security and thereby strengthening the economic security of the state and its territories. It is shown that on the basis of such an approach, the policy of consumer safety (as confirmed by the experience of the EU countries) allows solving such acute social and other problems of society as: production and consumption of safe and high-quality goods and services for humans; optimization and improvement of food consumption by the population; preventing the production, promotion and sale of counterfeit, contraband and counterfeit products; disposal of product residues and minimization of environmental pollution; environmentally friendly production and the sphere of consumer services; sustainable development of territories, etc. The directions of influence and connections between the implementation of the consumption security policy and the strengthening of the components (primarily food, social, environmental and informational) and the general state of the state’s economic security are determined. The priorities of the consumer safety policy at different levels of the economic management hierarchy have been determined, the implementation of which will allow institutionalizing and ensuring high efficiency of the consumer safety policy implementation and modernizing the economic security system of Ukraine due to this.